VD_FINDINFO ACH 130/11 - 24/2012 vom 7. Februar 2012 - VD Tribunal cantonal (2012)
INDEMNITÉ DE CHÔMAGE, DURÉE DU DROIT À LA PRESTATION D'ASSURANCE | 27 LACI, 61 let. a LPGA, 41b OACI, 94 al. 1 let. c LPA-VD